Acute inorganic nitrate intake increases regional insulin action in the brain: Results of a double-blind, randomized, controlled cross-over trial with abdominally obese men - Jordi P.D. Kleinloog; Ronald P. Mensink; Ellen T.H.C. Smeets; Dimo Ivanov; Peter J. Joris (NeuroImage: Clinical, 2022)
Aims: Improving brain insulin sensitivity may be a promising approach in the prevention and treatment of metabolic and cognitive diseases. Our aim was to investigate acute effects of inorganic nitrate on regional cerebral blood flow (CBF) responses to intranasal insulin in abdominally obese men. Methods: Eighteen apparently healthy men, aged 18–60 years and with a waist circumference ≥ 102 cm, participated in a randomized, double-blind, placebo-controlled cross-over trial. The study consisted of two test days separated by at least one week. Men received in random order a drink providing 10 mmol (i.e., 625 mg nitrate) potassium nitrate or an isomolar placebo drink with potassium chloride. Brain insulin action was assessed 120–150 min after the drinks by quantifying acute effects of nasal insulin on regional CBF using arterial spin labeling Magnetic Resonance Imaging. Glucose and insulin concentrations were measured at regular intervals, while blood pressure was determined fasted and at 240 min. Results: Inorganic nitrate intake increased regional insulin action in five brain clusters. The two largest clusters were located in the right temporal lobe (ΔCBF: 7.0 ± 3.8 mL/100 g/min, volume: 5296 mm3, P < 0.001; and ΔCBF: 6.5 ± 4.3 mL/100 g/min, volume: 3592 mm3, P < 0.001), while two other cortical clusters were part of the right frontal (ΔCBF: 9.0 ± 6.0 mL/100 g/min, volume: 1096 mm3, P = 0.007) and the left parietal lobe (ΔCBF: 6.1 ± 4.3 mL/100 g/min, volume: 1024 mm3, P = 0.012). One subcortical cluster was located in the striatum (ΔCBF: 5.9 ± 3.2 mL/100 g/min, volume: 1792 mm3, P < 0.001). No effects of nitrate were observed on CBF before administration. Following nitrate intake, circulating nitrate plus nitrite concentrations increased over time (P = 0.003), but insulin and glucose concentrations and blood pressure did not change. Conclusion: Acute inorganic nitrate intake may improve regional brain insulin action in abdominally obese men. These regions are involved in the regulation of different metabolic and cognitive processes.The trial was registered on January 6th, 2021 at ClinicalTrials.gov as NCT04700241.